Vaginal metastasis of renal clear cell carcinoma: a case report emphasizing the role of immunohistochemistry in differential diagnosis in the absence of a clinical history - Stolnicu, Simona; Patrichi, Andrei; Rozsnyai, Francisc; Soslow, Robert A. (Polish Journal of Pathology, 2023)
We present the case of a 71-year-old patient, with vaginal bleeding, dyspnea, headache, loss of appetite and weakness. Clinical examination revealed a pediculated vaginal mass of 25 mm diameter, of dark-red color and soft spongy consistency, with an ulcerated surface and originating from the anterior wall, which was surgically removed. The morphology was dominanted by large, round to polygonal tumor cells, arranged in a predominantly tubulo-cystic architecture, surrounding numerous blood vessels that dominated the appearance, suggesting a perivascular epithelioid cell tumor (PEComa) or hemangioblastoma but the presence of pleomorphic nuclei, numerous mitoses together with immunohistochemistry helped for a correct diagnosis of vaginal .